Coronary heart disease, heart failure, and the risk of dementia: A systematic review and meta-analysis - Wolters, Frank J; Segufa, Reffat A; Darweesh, Sirwan K L; Bos, Daniel; Ikram, Mohammad Arfan; Sabayan, Behnam; Hofman, Albert; Sedaghat, Sanaz (Alzheimer's & dementia, 2018)
Cardiovascular risk factors are closely linked with dementia risk, but whether heart disease predisposes to dementia is uncertain. We systematically reviewed the literature and meta-analyzed risk estimates from longitudinal studies reporting the association of coronary heart disease (CHD) or heart failure (HF) with risk of dementia. We identified 16 studies (1,309,483 individuals) regarding CHD, and seven studies (1,958,702 individuals) about HF. A history of CHD was associated with a 27% increased risk of dementia (pooled relative risk [RR] [95% confidence interval, CI]: 1.27 [1.07-1.50]), albeit with considerable heterogeneity across studies (I = 80%). HF was associated with 60% increased dementia risk (pooled RR 1.60 [1.19-2.13]) with moderate heterogeneity (I = 59%). Among prospective population-based cohorts, pooled estimates were similar (for CHD, RR 1.26 [1.06-1.49], nine studies; and HF, RR 1.80 [1.41-2.31], four studies) and highly consistent (I = 0%). CHD and HF are associated with an increased risk of dementia.